(untitled) (Sirte University Journal of Humanities, 2026)
The study aims to determine the degree of talent management practice in Aljomhoria bank - Benghazi city. For the study purpose, the researcher adopted analytical, statistical method using on a sample of (53) employees, She also utilized a questionnaire as a tool of gathering the basic data. The collected data was analyzed by SPSS software. The study concluded that the level of practicing talent management in Aljomhoria bank was very high following talent maintenance. Subsequently, the level of talent development came second. Finally, the level of talent recruitment came, which was moderate. However, it found out efficient talent management practice, with all its dimensions, at significance level of (.05). The researcher recommends the bank to promote practicing talent management, and make those in charge focus on such management. The bank should also provide talent-related techniques of recruitment and training and address the turnover issue.